2015
DOI: 10.3174/ajnr.a4350
|View full text |Cite
|
Sign up to set email alerts
|

Residual Thromboembolic Material in Cerebral Arteries after Endovascular Stroke Therapy Can Be Identified by Dual-Energy CT

Abstract: BACKGROUND AND PURPOSE: Dual-energy CT features the opportunity to differentiate among up to 3 different materials because the absorption of x-rays depends on the applied tube voltage and the atomic number of the material. For example, it is possible to distinguish between blood-brain barrier disruption and an intracerebral hemorrhage following treatment for a stroke. The aim of this study was to evaluate whether dual-energy CT is capable of distinguishing intra-arterial contrast agent from residually clotted … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 28 publications
0
6
0
Order By: Relevance
“…Recent medical literature advocates DECT for detecting residual peripheral intra-arterial thrombus after mechanical thrombectomy. 24 In the immediate postembolectomy setting, conventional residual thrombus on virtual non-contrast images shows a significantly higher attenuation relative to the perfused arteries but importantly not on the weighted average images (reconstructed conventional image) or iodine map. 23,25 Conversely, ISFT will be of low attenuation on virtual non-contrast images but will show higher attenuation on weighted average images and iodine map.…”
Section: Discussionmentioning
confidence: 92%
“…Recent medical literature advocates DECT for detecting residual peripheral intra-arterial thrombus after mechanical thrombectomy. 24 In the immediate postembolectomy setting, conventional residual thrombus on virtual non-contrast images shows a significantly higher attenuation relative to the perfused arteries but importantly not on the weighted average images (reconstructed conventional image) or iodine map. 23,25 Conversely, ISFT will be of low attenuation on virtual non-contrast images but will show higher attenuation on weighted average images and iodine map.…”
Section: Discussionmentioning
confidence: 92%
“…38 VNC images can also be used on post-EVT CT head to subtract residual contrast in the arteries and identify residual arterial thromboembolic material. 43 An in vitro study has demonstrated that VME techniques can differentiate red blood cell- and fibrin-rich clot that would have potential for predicting outcomes in thrombolysis or inform which device is best for clot retrieval in EVT. 44…”
Section: Ischemic Strokementioning
confidence: 99%
“…As with the VNC reconstructions from CT angiography, hyperdense arteries can be detected; however, no evaluation of the VNC with regard to the detection of early infarctions was performed, which is at least equally important in the acute stages [ 41 ]. In the second in vivo study, there was no comparison of arteries with residual clot material to the “gold-standard,” TICI scoring (thrombolysis in cerebral infarction), although conventional angiography studies were available [ 42 ]. The results about clot composition of artificial clots have yet to be verified in vivo [ 43 , 44 ].…”
Section: Clot Imagingmentioning
confidence: 99%
“…Arteries with clot material were significantly denser than perfused arteries on the VNC only (Fig. 4 ) [ 42 ].
Fig.
…”
Section: Clot Imagingmentioning
confidence: 99%